SCIATIC NERVE CONDUCTION VELOCITY AND LOCOMOTORY PATTERNS IN FROG, UROMASTIX AND RABBIT - S. Ahmed; S. Malik; M. A. Azeem; S. Noushad (Journal of Animal and Plant Sciences, 2012)
The complex interactions among the structural features of axon, its myelin sheath and its length, determine the nature of nerve impulse conduction.. In addition, fibers of different diameters and degree of myelination determine the nerve conduction velocity (NCV). It is therefore, hypothesized that for the same nerve, the NCV may differ in animals, due to the differences in the leg architecture and its movement during locomotion. The purpose of this study was to compare right and left limb’s sciatic NCV in three different classes of animals to identify differences, if any, and to relate these differences with different types of gait locomotry pattern observed in them. The Compound Action Potential (CAP) was recorded from both the right and left isolated sciatic nerves from adult Frog, Uromastix and Rabbit of both sexes. through Power Lab and its accessories. These CAP records were then used for the calculation of NCV, Significant difference was observed in sciatic NCV being greater in order of Frog>Rabbit>Uromastix. These differences were found well correlated with differences in their gait and locomotion. However, there was no significant difference among right and left sciatic nerve’s NCV for both Uromastix and Rabbit, while it was significantly different for Frog. The differences in NCV among Frog, Uromastix and Rabbit’s sciatic nerves reflect differences in these animals for their sciatic nerve diameter, leg architecture, gait and locomotion, as per their habitat.
Keywords: Compound Action Potential (CAP); Nerve Conduction Velocity (NCV); Sciatic Nerve; locomotion.